Evaluating the potential for exposure to organisms of public health concern in naturally occurring bathing waters in Europe: A scoping review. (1st November 2021) - Farrell, Maeve Louise; Joyce, Aoife; Duane, Sinead; Fitzhenry, Kelly; Hooban, Brigid; Burke, Liam P.; Morris, Dearbháile
Highlights: Europe-wide analysis of organisms of public health concern in bathing waters. Critical lack of surveillance of pathogenic organisms in bathing water is evident. Need to integrate current monitoring methods with more inclusive parameters. Highlight's health risk from organisms undetected by current regulatory methods. Greater understanding of health risk associated with bathing waters is needed. Abstract: Globally, water-based bathing pastimes are important for both mental and physical health. However, exposure to waterborne organisms could present a substantial public health issue. Bathing waters are shown to contribute to the transmission of illness and disease and represent a reservoir and pathway for the dissemination of antimicrobial resistant (AMR) organisms. Current bathing water quality regulations focus on enumeration of faecal indicator organisms and are not designed for detection of specific waterborne organisms of public health concern (WOPHC), such as antimicrobial resistant (AMR)/pathogenic bacteria, or viruses. This investigation presents the first scoping review of the occurrence of waterborne organisms of public health concern (WOPHC) in identified natural bathing waters across the European Union (EU), which aimed to critically evaluate the potential risk of human exposure and to assess the appropriateness of the current EU bathing water regulations for the protection of public health. Accordingly, this review sought to identify and synthesise all literature pertaining to a selection of bacterial (C ampylobacter spp., Escherichia coli, Salmonella spp., Shigella spp., Vibrio spp., Pseudomonas spp., AMR bacteria), viral (Hepatitis spp., enteroviruses, rotavirus, adenovirus, norovirus), and protozoan ( Giardia spp., and Cryptosporidium spp.) contaminants in EU bathing waters. Sixty investigations were identified as eligible for inclusion and data was extracted. Peer-reviewed investigations included were from 18 countries across the EU, totalling 87 investigations across a period of 35 years, with 30% published between 2011 and 2015. A variety of water bodies were identified, with 27 investigations exclusively assessing coastal waters. Waterborne organisms were classified into three categories; bacteria, viruses, and protozoa; amounting to 58%, 36% and 17% of the total investigations, respectively. The total number of samples across all investigations was 8, 118, with detection of one or more organisms in 2, 449 (30%) of these. Viruses were detected in 1281 (52%) of all samples where WOPHC were found, followed by bacteria (865(35%)) and protozoa (303(12%)). Where assessed (442 samples), AMR bacteria had a 47% detection rate, emphasising their widespread occurrence in bathing waters. Results of this scoping review highlight the potential public health risk of exposure to WOPHC in bathing waters that normally remain undetected within the current monitoring parameters. Grphical abstract: Image, graphical abstract